Indications and results of diagnostic biopsy in pediatric renal tumors: A retrospective analysis of 317 patients with critical review of SIOP guidelines. Issue 6 (12th February 2019) - de la Monneraye, Yvan; Michon, J.; Pacquement, H.; Aerts, I.; Orbach, Daniel.; Doz, F.; Bourdeaut, F.; Sarnacki, S.; Philippe‐Chomette, P.; Audry, G.; Coulomb, A.; Fréneaux, P.; et al.
Abstract: Objectives: According to the Renal Tumor Study Group (RTSG) of the International Society of Paediatric Oncology (SIOP), diagnostic biopsy of renal tumors prior to neoadjuvant chemotherapy is not mandatory unless the presentation is atypical for a Wilms tumor (WT). This study addresses the relevance of this strategy as well as the accuracy and safety of image‐guided needle biopsy. Methods: Clinical, radiological, and pathological data from 317 children (141 males/176 females, mean age: 4 years, range, 0–17.6) consecutively treated in one SIOP‐affiliated institution were retrospectively analyzed. Results: Presumptive chemotherapy for WT was decided for 182 patients (57% of the cohort), 24 (8%) were operated upfront, and 111 (35%) were biopsied at diagnosis. A non‐WT was confirmed after surgery in 5/182 (3%), 11/24 (46%), and 28/111 (25%), respectively. Age at diagnosis was the most commonly (46%) used criterion to go for biopsy but a nine‐year threshold should be retrospectively considered more relevant. Tumor volumes of clear cell sarcoma of the kidney and WT were significantly higher than those of other tumors ( P  = 0.002). The agreement between core‐needle biopsy (CNB) and final histology was 99%. No significant morbidity was associated with CNB. Conclusion: The use of SIOP criteria to identify patients eligible for presumptive WT neoadjuvant chemotherapy or upfront surgery avoided biopsy in 65% of children and led to a 97% rate of appropriate preoperative chemotherapy. Image‐guided CNB is a safe and accurate diagnostic procedure. The relevance of SIOP biopsy criteria might be improved by using an older age threshold (9 years instead of 6 years) and by adding initial tumor volume.